NILAI PENDIDIKAN KARAKTER DALAM PUISI “NIKMAT HIDUP” KARYA BUYA HAMKA - Sintia Rianti Siti Nurisa; Rochmat Tri Sudrajat; Yusep Ahmadi F (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Character education in Indonesia is an important thing for life and even for national identity. The creation of character education is not an easy thing, it needs a long process and self-confidence in building character well. Poetry is a literary work in which there are several values of character education that can be emulated.  In Hamka's poem "Nikmat Hidup", it contains a lot of character education values that can change the reader's behavior for the better. This study aims to describe the value of character education in Buya Hamka’s “Nikmat Hidup” (Enjoyment of Life) poem. The reason the researcher chose Hamka’s “Nikmat Hidup” poem was because this poems was interesting to study, then it is related to the fact that according to the researcher it could be used as a character formation for the reader. This study was analyzed using a qualitative descriptive technique, the Miles and Huberman model, which includes three steps that must be carried out, namely: data reduction, analysis, data presentation, and making conclusions. The results obtained from this research are there five values of character education in Buya Hamka’s poem “Nikmat Hidup”, including: religious values, honesty, hard work, independence, and social care.